Del sentir impersonal. Los estudios de Mario Perniola sobre la era estética - Hanza, Kathia (Pontificia Universidad Católica del Perú, 2017)
El artículo analiza la comprensión de la estética de Perniola. De acuerdo con este, el estudio de la estética (aísthesis), en tanto esfera del sentir, proporciona ciertas claves interpretativas para la comprensión del mundo contemporáneo, que secaracteriza por el empobrecimiento de la experiencia individual y la incapacidad para sentir propiamente. La conformación del sentir actual, que ha devenido impersonal, es explicada, por un lado, mediante la arqueología, que hace patentes las estratificaciones de lo ya sentido, y, por otro lado, mediante la genealogía, que descubre la dimensión activa del sentir.

The article analizes Perniola’s understanding of aesthetics. According to Perniola, the study of aesthetics (aísthesis) as a sphere of feeling provides interpretative clues for understanding of the contemporary world, characterized by theimpoverishment of individual experience and the incapacity for proper feeling. The conformity of feeling, which has become impersonal nowadays, is explained on the one hand through archaeology, which makes visible the stratifications of the “already felt”, and on the other hand, through genealogy, which discovers the active dimension of feeling.
On impersonal feeling. Mario Perniola’s studies on the aesthetics era
Keywords: Aísthesis; Arqueología; Estética; Genealogía; Sentir; Aísthesis; Aesthetics; Archaeology; Genealogy; Feel; https://purl.org/pe-repo/ocde/ford#6.00.00